2017
DOI: 10.1002/ldr.2685
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of the Effect of Bench Terraces on Runoff and Sediment Yield by Swat Modeling in a Small Semi‐arid Watershed in Northern Tunisia

Abstract: In Tunisia, soil and water conservation interventions are among the most practicable strategies to prevent and mitigate rainwater losses through surface runoff and consequential erosion of fertile soils. In this study, a small and terraced agricultural catchment (Sbaihia) was used as an experimental site to analyze and parameterize the effects of bench terraces on water and sediment yield using the Soil and Water Assessment Tool. Model calibration and validation was performed, taking advantage from high‐qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 30 publications
1
22
0
1
Order By: Relevance
“…The evaluation coefficients of the simulated daily runoff of the different objective functions for both the TW and UW indicated satisfactory model fit according to the assessment criteria (Moriasi et al 2007). The NSE values found in the UW and the TW agree with Khelifa et al (2016) who studied the impact of SWC on runoff and sediment yield in Tunisia. These authors report NSE values for runoff simulations using SWAT of 0.64 and 0.68 for calibration and validation, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The evaluation coefficients of the simulated daily runoff of the different objective functions for both the TW and UW indicated satisfactory model fit according to the assessment criteria (Moriasi et al 2007). The NSE values found in the UW and the TW agree with Khelifa et al (2016) who studied the impact of SWC on runoff and sediment yield in Tunisia. These authors report NSE values for runoff simulations using SWAT of 0.64 and 0.68 for calibration and validation, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Strohmeier et al (2015) reported that at plot scale, stone bunds reduced soil loss by 40% in the Gumara-Maksegnit watershed. In another study conducted in northern Tunisia on the effects of soil and water conservation structures on sediment load, Khelifa et al (2016) who estimated an overall soil loss reduction by 25%. The sediment yield estimated by SWAT model for the UW (44.8 t ha −1 year −1 ) and TW (33.5 t ha −1 year −1 ) was in agreement with other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results highlighted the ongoing dynamics of abandonment of agricultural terraces in relation to their main causes and effects. Khelifa et al () considered a small and terraced agricultural catchment (Sbaihia, Northern Tunisia) as an experimental site to analyse and parameterize the effects of bench‐terraces on water and sediment yield using the Soil and Water Assessment Tool. The results indicated that the local terraces, established on approximately 50% of the watershed area, reduced surface run‐off by around 19% and sediment yield by around 22%, decelerating the siltation of a highland lake.…”
Section: Overview Of the Papers In This Special Issuementioning
confidence: 99%
“…Esses modelos foram desenvolvidos com o objetivo de avaliar a ocorrência de processos hidrossedimentológicos em diferentes escalas temporais e espaciais, com a possibilidade de inferir sobre diversos cenários. Dentre os modelos hidrossedimentológicos existentes, o SWAT (Soil and Water Assessment Tool) desenvolvido pelo Agricultural Research Service of the United States Departament of Agricultural (ARS -USDA), tem se destacado pela ampla utilização em todo o mundo (Gassman et al, 2007;Bressiani et al, 2015;Strehmel et al, 2016;Vigiak et al, 2016;Pereira et al, 2016b;Khelifa et al, 2017;Tirupathi et al, 2018).…”
Section: Introductionunclassified